Spondyloarthritides: Theories and beyond - Kocatürk, Begüm; Balık, Zeynep; Pişiren, Gaye; Kalyoncu, Umut; Özmen, Füsun; Özen, Seza (Frontiers in Pediatrics, 2022)
Spondyloarthritides (SpA) are a family of interrelated rheumatic disorders with a typical disease onset ranging from childhood to middle age. If left untreated, they lead to a severe decrease in patients’ quality of life. A succesfull treatment strategy starts with an accurate diagnosis which is achieved through careful analysis of medical symptoms. Classification criterias are used to this process and are updated on a regular basis. Although there is a lack of definite knowledge on the disease etiology of SpA, several studies have paved the way for understanding plausible risk factors and developing treatment strategies. The significant increase of HLA-B27 positivity in SpA patients makes it a strong candidate as a predisposing factor and several theories have been proposed to explain HLA-B27 driven disease progression. However, the presence of HLA-B27 negative patients underlines the presence of additional risk factors. The current treatment options for SpAs are Non-Steroidal Anti-Inflammatory Drugs (NSAIDs), TNF inhibitors (TNFis), Disease-Modifying Anti-Rheumatic Drugs (DMARDs) and physiotherapy yet there are ongoing clinical trials. Anti IL17 drugs and targeted synthetic DMARDs such as JAK inhibitors are also emerging as treatment alternatives. This review discusses the current diagnosis criteria, treatment options and gives an overview of the previous findings and theories to clarify the possible contributors to SpA pathogenesis with a focus on Ankylosing Spondylitis (AS) and enthesitis-related arthritis (ERA).